Multistage interference cancellation with diversity reception for asynchronous QPSK DS - Jianfeng Weng
This paper introduces a multistage interference cancellation (MIC) technique with diversity reception for quadrature phase shift keying (QPSK) asynchronous direct-sequence code division multiple access (DS/CDMA) systems over frequency-selective multipath Rayleigh fading channels. Unlike the previous MIC, which tries to remove the lump sum of the multiple-access interference (MAI) and self-interference (SI), this introduced MIC attempts to cancel only the MAI and part of the SI due to the intersymbol interference, while treating the remaining SI created by the current symbol as useful information for symbol decision. In this technique, the RAKE combining is used to collect signal replicas over multiple fading paths. Upper and lower bounds on the bit error probability are derived using a Gaussian approximation and the characteristic function method. Furthermore, effects of channel estimation error on the performance are studied. Analytical and simulation results show that the introduced MIC can provide a performance extremely close to that in an ideal single-user environment and outperforms the previous MIC even in the presence of channel estimation error
Keywords: DS/CDMA systems; Gaussian approximation; QPSK; RAKE combining; Rayleigh fading channels; Asynchronous direct-sequence code division multiple access; Bit error probability; Channel estimation error effects; Characteristic function method; Diversity reception; Frequency-selective multipath fading channels; Intersymbol interference; Multiple-access interference; Multistage interference cancellation; Quadrature phase shift keying; Self-interference.; Symbol decision